English Listening as a Digital Literacy Practice: An Analysis of EFL Students' Informal Listening Habits in Indonesia - Nur Istiqamah; Moh Masduki; Abas Wismoyo Hernawan (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This study examines the informal listening habits of EFL students in Indonesia through the lens of digital literacy. Employing a descriptive quantitative survey method with 156 students from various academic programs, it investigates the types of content selected, underlying motivations, self-regulation strategies, and perceived affective impacts. The findings reveal that music, YouTube vlogs, and podcasts are the most frequently consumed content, primarily accessed via YouTube, Spotify, and TikTok. Content selection is driven by personal interest, entertainment, and convenience, consistent with Uses and Gratifications theory. From a digital literacy perspective, students are not merely passive consumers but active agents negotiating their linguistic identities through engagement with global content. The study concludes that informal listening is not simply a recreational activity but an integral component of the language learning ecosystem in the digital age. A key practical implication is the need to integrate informal listening practices into English language learning in Indonesia to make the curriculum more relevant to the realities of the digital generation living within a global media ecosystem.